Intraluminal Gist, A Rare Cause of Ileo-Ileal Intussusseption in an Elderly Male - Randhawa, Muhammad Afzal; Kaynat, Saba; Niaz, Hafsa; Shahzad, Tehseen (Archives of Clinical and Biomedical Research, 2018)
Introduction: Gastrointestinal stromal tumors are mesenchymal tumors found in the stomach, jejunum and ileum and represent 9% of all small bowel tumors. Their intraluminal occurrence in the small bowel is a rare phenomenon as they predominantly grow extra-luminally, so rarely causing small bowel obstruction or intussusception. However, intraluminal presence can provide a lead point for intussusception as does the other benign and malignant diseases such as inflammatory bowel disease, post-op adhesions, crohn’s disease, Meckle’s diverticulum, Lipoma, lymphoma, adenocarcinoma, metastatic neoplasm or even presence of intestinal tubes. In adults only 8-20% cases of intussusceptions are idiopathic while the rest of cases are secondary to an underlying pathology. In elderly population most cases are of Ileo-colic type of intussusception secondary to malignant disease especially adenocarcinoma and lymphomas. However, there is no sufficient data available previously of intraluminal GIST causing ileo-ileal intussusception which makes our case worth presenting to literature. Presentation: An elderly male patient of 67 years age presented with signs and symptoms of small bowel obstruction, weight loss and mild anemia. These symptoms started 3 months back and were slowly progressive. On examination he had a diffuse lower abdominal mass with signs of obstruction. Systemic examination was unremarkable and the patient had no co-morbid conditions. Exploratory laparotomy was carried out after radiological and baseline investigation and a diagnosis of intraluminal growth causing ileo-ileal intussusception confirmed. Primary anastomosis after resection of the involved segment done Histopathology showed GIST of low malignant potential with resection margins free of tumors and no lymph node involvement. Discussion: CT-scan abdomen is investigation of choice to d